Bernardino Baldi's In mechanica Aristotelis problemata exercitationes - Elio Nenci (Sources 3: Max Planck Research Library for the History and Development of Knowledge, 2011)
_In mechanica Aristotelis problemata exercitationes_ written by Bernardino Baldi is reprinted with an introduction and commentary as the third volume of the series _Sources of the Max Planck Research Library for the History and Development of Knowledge._ The volume is also freely available in electronic form as an open-access publication on the Internet at www.edition-open-access.de. The _Exercitationes_ were first published in 1621, four years after the death of the author. The work belongs to the long tradition of studies on the pseudo-Aristotelian _Mechanical Problems_ developed during the Renaissance but, unlike most other works written during the sixteenth century, it takes a critical position against the theoretical approach of the pseudo-Aristotelian text. The _Exercitationes_ display a systematic application of Archimedean principles to the explanation of the questions discussed in _Mechanical Problems_ illustrating the patchwork character of preclassical mechanics. Moreover, Baldi's work presents lengthy digressions that considerably widen the boundaries of mechanics.